A multifunctional nano-therapeutic platform based on octahedral yolk-shell Au NR@CuS: Photothermal/photodynamic and targeted drug delivery tri-combined therapy for rheumatoid arthritis. (October 2021) - Huang, Ruqi; Zhang, Caiyi; Bu, Yeyang; Li, Zheng; Zheng, Xin; Qiu, Shang; Machuki, Jeremiah Ong'achwa; Zhang, Lijie; Yang, Yun; Guo, Kaijin; Gao, Fenglei
Abstract: Rheumatoid arthritis (RA) is a common chronic autoimmune disease that results from synovial hyperplasia. The hyperplasia of synovium directly degrades cartilage by secreting matrix-degrading enzymes and inducing cartilage degradation and even loss of joint function. In this study, a metal/semiconductor composite, octahedral copper sulfide shell, and gold nanorod core (Au NR@CuS) is designed for, photothermal therapy (PTT), photodynamic therapy (PDT), and chemotherapy (CT) combination therapy for RA to remove hyperplasia of the synovium. Upon laser irradiation, the coupling of the local surface electromagnetic field improves the electromagnetic field of the Au NR core and the absorption of light of the CuS shell, whereby the photothermal effect is enhanced. Due to the Fenton-like reactions and the integration of Au NR and CuS semiconductor photocatalyst inhibits hole recombination and provides a reaction site for photocatalysis, which introduces additional OH to photodynamics therapy. In addition, the large octahedral void space in Au NR@CuS NPs can be used for loading a high quantity of drugs for chemotherapy, and modified with vasoactive intestinal peptide and hyaluronic acid (HA) formation VIP-HA-Au NR@CuS NPs to target synovial cells in RA. Under combination therapy, VIP-HA-Au NR@CuS NPs were shown to effectively inhibit the synovial cells and the edema degree of the CIA mouse was alleviated apparently. Both in vitro and in vivo studies indicate that the VIP-HA-Au NR@CuS NPs can provide a potential possibility for the treatment of RA.